Assessing the Quality of Life Using the Health Utilities Index Questionnaire in Children With Severe Persistent Asthma During the Treatment With Omalizumab - Leyla S. Namazova-Baranova; Elena A. Vishnеva; Elena A. Dobrynina; Irina V. Vinyarskaya; Anna A. Alekseeva; Vladislav V. Chernikov; Lilia R. Selimsianova (Union of pediatricians of Russia, 2017)
Background. Quality of life (QoL) is an important parameter that provides additional information about changes in health status. Objective. Our aim was to study the change in QoL of patients with severe persistent bronchial asthma (BA) during the treatment with genetically engineered biological preparation (GIBP) omalizumab in addition to daily background therapy. Methods. The QoL assessment was conducted using the Health Utilities Index Mark 3 and Mark 2 (HUI3, HUI2) questionnaires at two points (1st point and 2nd point - in 6 months) in 47 children with severe BA at the age of 13 (7; 17) years, 72% of them are boys. At the same points, QoL was evaluated using the PAQLQ (S) specialized pediatric questionnaire (Standardized Pediatric Asthma Quality of Life Questionnaire). Results. Depending on the duration of omalizumab therapy, all children were divided into 5 groups: 1st group - children who did not receive treatment with monoclonal antibodies at the 1st point; in 2, 3, 4, 5-th groups, the QoL assessment was performed on GIBP treatment for different time. In children of the 1st group whose QoL was evaluated before starting GIBP therapy and in 6 months, a statistically significant change in scores on the Health Utilities Index questionnaire was noted: the multi-attribute indices HUI2 and HUI3 improved, respectively, by 21.3 and 10.71% (p = 0.041 and 0.086). According to the HUI2 classification system, a significant improvement in the emotion attribute was revealed, which positively correlated with the overall indicator and the emotion indicator of the PAQLQ (S) questionnaire. In the remaining groups, the indicators of the Health Utilities Index questionnaire did not change significantly. Conclusion. The study results showed that the dynamics of the quality of life in children with severe persistent BA is an important additional criterion in a comprehensive assessment of the efficacy of targeted bioengineering therapy.